Leveraging in vitro and pharmacokinetic models to support bench to bedside investigation of XTMAB-16 as a novel pulmonary sarcoidosis treatment - Offman, Elliot; Singh, Noopur; Julian, Mark W.; Locke, Landon W.; Bicer, Sabahattin; Mitchell, Jonah; Matthews, Thomas; Anderson, Kirsten; Crouser, Elliott D. (Frontiers in Pharmacology, 2023)
Background: Sarcoidosis is a chronic, multisystem inflammatory disorder characterized by non-caseating epithelioid granulomas; infiltration of mononuclear cells; and destruction of microarchitecture in the skin, eye, heart, central nervous system, and lung in >90% of cases. XTMAB-16 is a chimeric anti-tumor necrosis factor alpha (TNFα) Ab, distinct from other anti-TNF Ab based on its molecular structure. The efficacy of XTMAB-16 has not been demonstrated, and it is still undergoing clinical development as a potential treatment for sarcoidosis. The current study demonstrates the activity of XTMAB-16 in a well-established in vitro sarcoidosis granuloma model, although XTMAB-16 is not yet approved by the United States Food and Drug Administration (FDA) for treatment of sarcoidosis, or any other disease. Objective: To provide data to guide safe, efficacious dose selection for the clinical development of XTMAB-16 as a potential treatment for sarcoidosis. Methods: First, XTMAB-16 activity was evaluated in an established in vitro model of granuloma formation using peripheral blood mononuclear cells from patients with active pulmonary sarcoidosis to determine a potentially efficacious dose range. Second, data obtained from the first-in-human study of XTMAB-16 (NCT04971395) were used to develop a population pharmacokinetic (PPK) model to characterize the pharmacokinetics (PK) of XTMAB-16. Model simulations were performed to evaluate the sources of PK variability and to predict interstitial lung exposure based on concentrations in the in vitro granuloma model. Results: XTMAB-16 dose levels of 2 and 4 mg/kg, once every 2 weeks (Q2W) or once every 4 weeks (Q4W) for up to 12 weeks, were supported by data from the nonclinical, in vitro secondary pharmacology; the Phase 1 clinical study; and the PPK model developed to guide dose level and frequency assumptions. XTMAB-16 inhibited granuloma formation and suppressed interleukin-1beta (IL-1beta) secretion in the in vitro granuloma model with a half maximal inhibitory concentration (IC50) of 5.2 and 3.5 µg/mL, respectively. Interstitial lung concentrations on average, following 2 or 4 mg/kg administered Q2W or Q4W, are anticipated to exceed the in vitro IC50 concentrations. Conclusions: The data presented herein provide a rationale for dose selection and support the continued clinical development of XTMAB-16 for patients with pulmonary sarcoidosis.